Civic passions : seven who launched progressive America (and what they teach us) - Tichi, Cecelia, 1942- (University of North Carolina Press, 2009)
Tichi examines innovative leadership in periods of crisis in American history, starting from the late 19th century, when respected voices warned that America was on the brink of collapse. She brings 7 iconoclastic individuals from the Gilded Age back to life to show how citizen-activists can engage the problems of the age in imaginative ways. This is a provocative and powerfully written social history, a collection of minibiographies, and a user's manual on how a generation of social reformers can turn peril into progress with fresh, workable ideas.